2020
DOI: 10.14214/sf.10051
|View full text |Cite
|
Sign up to set email alerts
|

The role of state-owned commercial forests and firm features in nature-based tourism business performance

Abstract: Nature-based tourism (NBT) is a growing industry within regions rich in natural amenities worldwide. An important feature of NBT business is the dependence on the quality of surrounding environment. This paper addresses the role of the management of commercial forests owned by the state in Finnish Lapland. The paper explores the NBT entrepreneurs’ willingness to participate in a proposed new landscape and recreational value trading (LRVT) and elaborates the effect of entrepreneur and enterprise characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The findings by McCline et al (2000) and Nybakk and Hansen (2008) revealed that variables, such as risk willingness and recognition of opportunities, also influenced business performance and were able to differentiate entrepreneurs from nonentrepreneurs. Likewise, other researchers revealed that willingness to take risks (Madichie & Gbadamosi, 2017) and the ability to recognise business opportunities (Chang & Chen, 2020) are critical requirements of a successful entrepreneur, which also influence business performance (Kosenius et al, 2020). Therefore, these discussions lead to the establishment of the following hypotheses: H1: 'Risk Willingness' of EAO has a positive effect on business owner's performance.…”
Section: Entrepreneurial Attitude Orientation (Eao)mentioning
confidence: 96%
“…The findings by McCline et al (2000) and Nybakk and Hansen (2008) revealed that variables, such as risk willingness and recognition of opportunities, also influenced business performance and were able to differentiate entrepreneurs from nonentrepreneurs. Likewise, other researchers revealed that willingness to take risks (Madichie & Gbadamosi, 2017) and the ability to recognise business opportunities (Chang & Chen, 2020) are critical requirements of a successful entrepreneur, which also influence business performance (Kosenius et al, 2020). Therefore, these discussions lead to the establishment of the following hypotheses: H1: 'Risk Willingness' of EAO has a positive effect on business owner's performance.…”
Section: Entrepreneurial Attitude Orientation (Eao)mentioning
confidence: 96%
“…However, it should be noted that the arrival of tourists in rural areas can contribute to the gentrification of tourism [30], which is currently happening in the north of Iran, where the Hyrcanian Forests are located. Forests are critical for tourism income [31], and nature-based tourism is often included in forest strategies [32]. Tourism connected to forests would be more beneficial for rural areas than for the forests themselves [33].…”
Section: Cloud Ocean Sites and Hyrcanian Forests Tourism Potentialmentioning
confidence: 99%
“…In the Nordics, activities take place in forests, mountain areas, rivers and lakes and include a large range of services, for example, accommodation, adventure activities, fishing, hunting, educational courses and activities related to food [60,61]. On average, this type of enterprise offers five different services, and are typically rural microenterprises with labour-intensive activities based on local environmental knowledge [62]. Agritourism enterprises are a different type of tourism business that offer farm accommodation and activities.…”
Section: Nature-based Enterprisesmentioning
confidence: 99%